KOMUNIKASI KRISIS TERKAIT REGULASI JHT PADA KEMENTERIAN KETENAGAKERJAAN RI DILIHAT DARI KRONOLOGIS, TAHAPAN, DAN TIPOLOGI KRISIS. - Ikhsannul Ardief (Jurnal Komunikasi dan Budaya, 2023)
Government regulations related to the procedures and requirements for payment of Old Age Security (JHT) are the responsibility of the government in order to create the best solution for the government and its target public. The enactment of Permenaker Number 2 of 2022 is a government regulation on the payment of Old Age Security (JHT) which is then considered a crisis. The purpose of the research is to find out the Chronology, Stages, and Crisis Typology of Permenaker Number 2 of 2022. Research methodology through a qualitative case study approach. The results showed that in the Crisis Chronology which includes pre-crisis (the Ministry of Manpower has not realized the existence of a crisis even though there are initial symptoms that have emerged), crisis (Public Relations of the Ministry of Manpower determines the crisis and acts and responds to the crisis), and post-crisis (the Ministry of Manpower conducts socialization, evaluation related to the issuance of a new Permenaker, namely Permenaker No. 4 of 2022 as a replacement for Permenaker Number 2 of 2022). Then the prodromal crisis stage (the Ministry of Manpower has not yet considered a crisis), the acute stage (determining as a crisis and transferring crisis resolution to the Crisis Handling Team consisting of the Ministry of Manpower Public Relations and related Technical Implementation Units), the Chronic Stage (the crisis is growing) Resolution Stage (Issued Permenaker No. 4 of 2022 as a replacement for Permenaker No. 2 of 2022 and evaluation of the new regulation. Finally, in the Crisis Typology, the Crisis of Permenaker No. 2 of 2022 is included in the Crisis of Human Climate-Confrontation. Keywords: permenaker RI; crisis chronology; crisis stages; crisis typology; JHT